Use of Instagram Stories Feature as Self Disclosure Media on @Azkhategar Account - Aulia Maharani; Poppy Febriana (LPPM Stikosa - AWS, 2024)
This study explores the use of Instagram Stories features as a self – disclosure media on @Azkhategar account. Self – disclosure is a form of communication in which individuals disclosure information to others. Through her Instagram account, Azkha actively self – disclosure with an average of 8 to 15 posts per day, showcasing aspects of herself such a lifestyle, fashion, and make – up. In its stories content, Azkha also collaborates with local brands to expand its audience reach. This study uses descriptive qualitative approach with non – participant observation and data analysis of Miles & Huberman model and the main theory used in this study is the theory of self – disclosure. The results showed that the use of Instagram Stories provides a platform for Azkha to strengthen her existence, build closeness with her followers and express herself creatively. In today’s digital context, social media such as Instagram plays an important role in facilatating self – disclosure and expanding individual social interactions. The findings provide valuable insights into how individuals utilize social media as a tool for sharing personal information and building self – image online. This research also contributes to the understanding of the use Instagram Stories in the context of self – disclosure.